2003
DOI: 10.1152/ajpgi.00312.2002
|View full text |Cite
|
Sign up to set email alerts
|

Differential mechanism and site of action of CCK on the pancreatic secretion and growth in rats

Abstract: Recent studies demonstrated that cholecystokinin (CCK) at physiological levels stimulates pancreatic enzyme secretion via a capsaicin-sensitive afferent vagal pathway. This study examined whether chemical ablation of afferent vagal fibers influences pancreatic growth and secretion in rats. Bilateral subdiaphragmatic vagal trunks were exposed, and capsaicin solution was applied. Pancreatic wet weight and pancreatic secretion and growth in response to endogenous and exogenous CCK were examined 7 days after capsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 41 publications
2
21
0
2
Order By: Relevance
“…The neural circuitries involving CCK1R of capsaicin-sensitive vagal afferent neurons, central synapses, and vagal cholinergic efferent fibers (represented in Fig. 6) were recently confirmed by Yamamoto et al (580). Although most of the information on the vagal CCK1R is obtained from research in animals, observations were reported in humans suggesting that CCK stimulates the pancreas via a pathway dependent on cholinergic innervation (35, 493).…”
Section: Exocrine Pancreasmentioning
confidence: 62%
“…The neural circuitries involving CCK1R of capsaicin-sensitive vagal afferent neurons, central synapses, and vagal cholinergic efferent fibers (represented in Fig. 6) were recently confirmed by Yamamoto et al (580). Although most of the information on the vagal CCK1R is obtained from research in animals, observations were reported in humans suggesting that CCK stimulates the pancreas via a pathway dependent on cholinergic innervation (35, 493).…”
Section: Exocrine Pancreasmentioning
confidence: 62%
“…Although camostat feeding may also increase the release of endogenous secretin (49), it is clear that it is CCK that is required for camostat-induced growth. The trophic effect of CCK in rats appears primarily to be through high-affinity CCK receptors (7) located on the acinar cells (53). The effect of the high-protein diet may be mediated by another hormone or neural pathway but also may be mediated by amino acids from the dietary protein.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that CCK-AR and CCK-BR regulate a number of physiological functions, e.g. gallbladder contraction [6] , pancreatic enzyme release [7] , gastric acid secretion [8] and pyloric sphincter closure [9,10] . In 1892, a special kind of cell which is now called "interstitial cells of Cajal" (ICC) in the gastrointestinal tract was first described by the famous Spanish neuro-histologist Ramony Cajal [11] .…”
Section: Introductionmentioning
confidence: 99%